IbM KELOMPOK PUPUK KOMPOS PEMUDA MANDIRI DI DESA BENGKEL KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Irianto Irianto; Rusli Amrul (Valid: Jurnal Ilmiah, 2017)
Science and Technology Program for Communities (IbM) Workshop held in village districts Labuapi West Lombok district, in cooperation with two business partners namely the compost "Youth Self" and the group "Amanah Farmer".Targets and outcomes to be achieved: 1) changing the mindset (mindset) effort compost (organic) can become a core business, not a sideline, 2) improving the skills of the group in the production process, so that the production / sales volumes increased by 25%, 3) skills upgrading business plans, financial records models, models of product packaging. As for the group "Amanah Farmer": 1) the requirement for inorganic fertilizer. 2) expected to be more interested farmers to use compost as compared to non-organic fertilizer for compost fertilizer prices much cheaper and safer for health. Method used: 1) training in management / entrepreneurship, 2) provide equipment and assistance garbage breaking machine usage, 3) assistance to create a model of financial records, packaging products. 4) facilitation prepare a business plan.The results showed that activity, there is a change of mindset in the management group of the Youth Self compost, is no longer a side job, but it will be a business activity to earn revenue. Total production increased by 44%. Packaging compost is better and easier to market. Meanwhile, Amanah Farmer groups, there is a paradigm shift in the use of inorganic fertilizer to organic fertilizer, and have an understanding of the negative impact of the use of inorganic fertilizer. Costs of production, particularly the use of fertilizers decreased by 65.51%, after the use of organic fertilizers. Both groups have a model financial records of the group, and be able to draw up a business plan (business plan) in developing a business